Bachelor of Science in Hospitality Management Students’ Perception on Student Council Activities at Bestlink College of the Philippines: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Learning and personal growth are achieved in college through academic and non-academic activities inside and outside the classroom. The student council continues to serve students by implementing college-wide impact projects and programs. Since a school year would only pass with being scrutinized at a general assembly, it has provided fairness and openness to the students. A Student Council is a group of elected and volunteer students who work with an adult advisor within the framework of a constitution or bylaws to provide a means for student expression and assistance in school affairs and activities, provide opportunities for student leadership experience, and promote student, faculty, and community relations. The student council's participation is necessary in connection with the hospitality management course, which frequently incorporates specific types of events. The perceptions of BSHM students toward Student Council activities at Bestlink College of the Philippines are at the heart of this research. The study's findings may aid student leaders since they will gain a comprehensive understanding of how the Student Council functions as a student organization. They may be able to evaluate which activities and projects will have the greatest influence on the welfare of students because they are future college leaders. This study utilized the descriptive method to investigate and collect information about the BSHM students' perception of student council activities at Bestlink College of the Philippines. The questionnaire was the major instrument in this descriptive qualitative study, with observation and interviews as supporting tools. The researcher gathered 50 students to complete our survey. The majority of the respondents are between the age of 21-24, mostly female students from BSHM who agreed to the activities made by the student council. The researchers developed instructions to improve the respondents' academic and non-academic performance by implementing the activities proposed by the student council based on the data acquired and conclusions reached. Guidelines include inviting students to engage in a survey regarding student council programs so that the student council may learn about the students' thoughts and improve their programs. The researchers advised programs that would be suitable for all students and would encourage them to participate. According to the researchers, students should engage with the student council to establish and improve the programs, and they should be inspired to be the future generation of leaders. These guidelines will give key elements in students' commitment to academic and non-academic achievement and motivate them with positive energy.
Keywords: Student council; new normal education; student perception; student leadership activities